Profile of Interpersonal Communication of Grade XII Science Student at SMA Negeri 1 Kediri - Khairunnisa, Inni (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine students' perceptions of interpersonal communication. This study is an exploratory research with research subjects of 57 grade XII Science students at SMA Negeri 1 Kediri. The research instrument used was a closed questionnaire with graded answers according to a Likert scale that had been validated and declared valid. The research data analysis used was descriptive statistics and inferential statistics with the Anova test at a significance level of 5%. The results of the study show that (1) grade XII Science students at SMA Negeri 1 Kediri have an average perception score about interpersonal communication on the indicator, namely Oppeness of 3.11 in the Tall category, Empathy is 3.27 in the Very High category, Supportiveness is 3.34 in the Very High category, Positiveness is 3.16 in the Very High category, and Equality is 3.20 in the Tall category; (2) there are significant differences in students' perceptions of interpersonal communication on the indicators of oppeness, empathy, supportiveness, positiveness, and equality as evidenced by a significance value of 0.003, which is smaller than 0.05 (<0.05).